The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1080/23802359.2018.1463826
|View full text |Cite
|
Sign up to set email alerts
|

Complete plastome sequence of Lilium pardalinum Kellogg (Liliaceae)

Abstract: Lilium pardalinum Kellogg is native to the Pacific Coast of the United States, and grows in woodland near streams. In the present study, the complete plastome of L. pardalinum was sequenced. The plastome sequence is 151,969 bp long with a large single copy, a small single copy, and two inverted repeat regions of length 81,401, 17,346, and 26,611 bp, respectively. A total of 133 genes were identified, including 82 coding genes, 8 ribosomal RNAs, 38 transfer RNAs, and 5 pseudoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Unfortunately, the phylogenetic position of the section using both markers was not resolved or was supported weekly. On the other hand, Kim et al [47] suggested that L. philadelphicum seems to be distinguishable from other species in the section based on phylogenomics using plastome sequences. This relationship is well supported by the 28 species trees constructed in this study.…”
Section: The Polyphyly Of Pseudoliriummentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the phylogenetic position of the section using both markers was not resolved or was supported weekly. On the other hand, Kim et al [47] suggested that L. philadelphicum seems to be distinguishable from other species in the section based on phylogenomics using plastome sequences. This relationship is well supported by the 28 species trees constructed in this study.…”
Section: The Polyphyly Of Pseudoliriummentioning
confidence: 99%
“…Reads exceeding 50 bp in length were extracted and used as raw reads after this step. Raw reads were mapped to the plastome sequence of Lilium pardalinum [47] with medium-low sensitivity. Reads were aligned to the reference then de novo assembled with zero mismatches and gaps among the reads to generate contigs.…”
Section: Sequencing Assembly and Annotationmentioning
confidence: 99%
“…This pattern is also consistent with hybridization. Based on chloroplast genome sequences of the two parental species (Kim and Lim 2018; Kim et al 2018), single nucleotide differences were expected in rbc L and the spacer between the psa I and ycf 4 genes. In order to determine the putative maternal parent of the hybrid, these two chloroplast (cpDNA) loci were sequenced.…”
Section: Oregonmentioning
confidence: 99%